(untitled) (International Journal of Engineering and Computer Science, 2014)
The internet protocol version 4 (IPV4) is depleting in address spaces day by day and hence the deployment of IPV6 in network is very essential. IPV6 is a new generation protocol that is expected to solve the issues that arise in IPV4 but also poses some security issues. The emphasis in this paper is to identify the vulnerabilities that come in IPV6 and how to remove those vulnerabilities. Reconnaissance attack is employed by attackers to fraudulently enter in IPv6 network. For this reason an unique and secured IPV6 address will be generated so that a secured network can be set up and malicious nodes would not enter the network. There are different type of techniques that are used like i-SeRP(IPV6 Security Risk Prototype), CGA(Cryptographically Generated addresses), Privacy Extension, SSAS (Simple Secure Addressing Scheme) to make the network secure. In this paper an unique secured IPV6 address will be generated to make network secure by using the combination of certification authority and PKI structure for node verification, Diffie Hellman for exchange of secrets.